2009
DOI: 10.1007/s12034-009-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

On stability of NiTi wire during thermo-mechanical cycling

Abstract: The use of NiTi wire as thermal actuator involves repeated thermal cycling through the transformation range under a constant or fluctuating load. The stability of the material under such conditions has been a concern for the past many years. Experimental results show that for a given alloy composition, the repetitive functional behaviour of NiTi wire is largely dependent on the processing schedule/parameters and the stress-strain regime of thermo-mechanical cycling (TMC). Among the various processing parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The stability of the microstructure ensured that progression of dislocations, and crack growth was slowed in the trained T-LP material, leading to the longer fatigue life than the LP material [12,29]. The nanocrystalline material impeded the dislocation activity of transformation induced plasticity, delaying crack initiation in these materials [45][46][47]. The majority of high cycle fatigue life in NiTi is in the crack initiation stage, with propagation occurring rapidly once the critical crack size is reached [48], which accounts for the uniformity of the fracture surfaces in Figure 11b and c. Brittle inclusions located at the surface serve as the crack initiation points [49].…”
Section: Thermal and Physical Propertiesmentioning
confidence: 99%
“…The stability of the microstructure ensured that progression of dislocations, and crack growth was slowed in the trained T-LP material, leading to the longer fatigue life than the LP material [12,29]. The nanocrystalline material impeded the dislocation activity of transformation induced plasticity, delaying crack initiation in these materials [45][46][47]. The majority of high cycle fatigue life in NiTi is in the crack initiation stage, with propagation occurring rapidly once the critical crack size is reached [48], which accounts for the uniformity of the fracture surfaces in Figure 11b and c. Brittle inclusions located at the surface serve as the crack initiation points [49].…”
Section: Thermal and Physical Propertiesmentioning
confidence: 99%
“…6a). With classical heat treatments, strain hardening are classically observed in cold worked material directly aged as in Saikrishna et al (2009) or annealed and aged as in Jiang et al (2009). Materials having linear and potentially elastic behaviour after transformation plateau, with important tensile strength, have already been observed in Pilch et al (2009) with Joule heating but have never been obtained with conventional heat treatments to the knowledge of authors.…”
Section: Brittle Behaviour Vs Strain Hardeningmentioning
confidence: 99%
“…This annealing condition ensures a large grain size -the amorphous bands start to crystallize without completely annealing the structural defects in the material, as crystallite nucleation is supressed [18]. This step is essential for the material to recover from any previous cold work or damage it has sustained and to stabilize transformation characteristics [18].…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Fatigue Ð Previous studies have reported on a continuous change in the functional properties of the NiTi such as the transformation temperatures, transformation hysteresis and strain response under thermo-mechanical cycling [18]. Our experimental work comprises 132 tests, which effectively subject the 3 test specimens to thermo-mechanical cycling throughout the study; hence, the stability of the material response is a concern.…”
Section: Predictions and Limitationsmentioning
confidence: 99%